A Goldilocks Theory of Fiscal Deficits - Mian, Atif; Straub, Ludwig; Sufi, Amir (American Economic Review, 2025)
We develop a tractable framework for deficit and debt dynamics. A “free lunch” fiscal deficit—one that raises spending without higher future taxes—is sustainable without zero lower bound (ZLB) only when R < G − φ, where φ is the sensitivity of the interest rate to the debt level. With the ZLB, both high and low deficits can increase debt, as the latter weaken demand and reduce nominal growth at the ZLB. A rise in income inequality expands fiscal space outside the ZLB, but contracts it at the ZLB. Calibrating the model, we find little space for “free lunch” policies for the United States in 2019, but significant space for Japan. (JEL D31, E23, E43, E62, H62, H63)